Spatial identification of regions exposed to multi-hazards at the pan-European level - T.-E. Antofie; T.-E. Antofie; S. Luoni; A. Tilloy; A. Sibilia; S. Salari; G. Eklund; D. Rodomonti; C. Bountzouklis; C. Corbane (Natural Hazards and Earth System Sciences)
The European Commission Disaster Risk Management Knowledge Centre (DRMKC) has developed and hosts a web platform, the Risk Data Hub (RDH), designed to facilitate access to and sharing of curated, EU-wide risk data, tools, and methodologies, ultimately supporting disaster risk management (DRM) initiatives. Based on the RDH data, we propose a methodology for the identification of regions with multi-hazard exposure at the pan-European level (EU27+UK). This methodology aims to support disaster risk management (DRM) decision-making processes at both national and subnational levels in the EU. By employing a meta-analysis approach and aggregating the hotspots of exposure to single hazards, we provide an objective, statistically robust assessment of the European multi-hazard landscape at the finest spatial subdivision level, local administrative units (LAUs). Our results suggest that 21.4 % of European LAUs are exposed to multiple natural hazards, affecting around 87 million people (18.8 % of the European population). Furthermore, nearly half this population is exposed to more than three hazards. We find that beyond population density, the income level (i.e. high, medium, low) is the primary driver that influences risk status at the local level, within both rural and urban areas. On average, we find higher multi-hazard exposure for people living in high-income urban areas or low-income rural areas. We further validate our results by comparing them with empirical data on fatalities and disaster events, revealing a relatively high correlation between statistically significant multi-hazard hotspots and fatalities (r=0.59). By providing a detailed assessment of multi-hazard exposure at the pan-European scale, this study contributes to a better integration of multi-hazard risks in European disaster risk management plans.